Неалкогольний стеатогепатіт на тлі метаболічного синдрому: патоморфологічні особливості - Чайка, Ю. І. (Clinical Endocrinology and Endocrine Surgery, 2012)
The analysis of 2912 necropsy indicated 1231 cases (42.3%) with signs of parenchymatous fatty dystrophy of hepatocytes. All cases of liver steatosis were analyzed according to the following criteria: age, sex, associated disease, cause of death, existence of metabolic syndrome, alcohol influence, viral hepatitis, histological activity index, stage of fibrosis. This made it possible to identify 362 cases (29.4%) with primary nonalcoholic steatohepatitis, which is the morphological equivalent of liver damage in metabolic syndrome. In carrying out morphological study of all cases of primary non-alcoholic steatohepatitis was found almost completely identical histological changes in the independence of the severity of symptoms of metabolic syndrome. This makes it possible to assert that the changes in liver occur already in the early stages of development of the metabolic syndrome.